The relationship between the competencies of a technology park and the competitiveness of its resident IT enterprises: a case analysis at TECNOPUC - Pardo, Wladimir Ribeiro; Becker, Grace Vieira; Hansen, Peter Bent; Ruas, Roberto Lima; Mônego, Henrique Meister (Revista de Administração da UFSM, 2015)
Over the years, technology parks have attracted organizations seeking competitiveness through innovation and technological cooperation. The aim of this study was to investigate the relationship between the competencies contained within a technology park, TECNOPUC, and the competitiveness of the Information Technology (IT) firms located within it. A qualitative exploratory study was conducted involving experts on the topic, the Park managers and managers from seven firms located in the Park. The findings reveal the perception that the brand TECNOPUC and the working environment provided by the Park are the competencies that are more closely related to the competitiveness of the firms located within it. The managers interviewed seem to be in the Park in search of business opportunities with large corporations, focusing their actions on reducing costs in order to achieve greater competitiveness. Rather than developing or selling technology, the priority seems to be selling products and services. Thus, actions aimed at encouraging and promoting research, technological development and innovations, such as the implementation of joint projects, for example, are not prioritized.